2016
DOI: 10.1007/s00431-016-2741-7
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal practice in extreme premature delivery: variation in Dutch physicians’ preferences despite guideline

Abstract: Decisions at the limits of viability about initiating care are challenging. We aimed to investigate physicians’ preferences on treatment decisions, against the background of the 2010 Dutch guideline offering active care from 24+0/7 weeks of gestational age (GA). Obstetricians’ and neonatologists’ opinions were compared. An online survey was conducted amongst all perinatal professionals (n = 205) of the 10 Dutch level III perinatal care centers. Response rate was 60 % (n = 122). Comfort care was mostly recommen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 34 publications
(69 reference statements)
1
40
0
Order By: Relevance
“…There is broad agreement in developed countries that all deliveries above 26 weeks should receive active perinatal care, whereas in 2011 there was greater variation at 24 and 25 weeks in France and elsewhere. For example, the attitudes of Dutch health care professionals varies most towards births at 24 and 25 weeks' gestation [35], and the largest differences in survival seen in five European regions were at 24 weeks' gestation, with much greater consistency in outcomes above this gestational age [36].…”
Section: Study Findings In Contextmentioning
confidence: 99%
“…There is broad agreement in developed countries that all deliveries above 26 weeks should receive active perinatal care, whereas in 2011 there was greater variation at 24 and 25 weeks in France and elsewhere. For example, the attitudes of Dutch health care professionals varies most towards births at 24 and 25 weeks' gestation [35], and the largest differences in survival seen in five European regions were at 24 weeks' gestation, with much greater consistency in outcomes above this gestational age [36].…”
Section: Study Findings In Contextmentioning
confidence: 99%
“…Statistics may not always be of additional value to parents. Boss found that physicians’ predictions of morbidity and death are not central to parental decision-making regarding delivery room resuscitation [ 33 ]. Janvier rightly appoints the disadvantages of using statistics, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…We developed the current survey in three stages just as described elsewhere. The first version was based on a combination of literature on prenatal counselling, several prenatal counselling surveys that were kindly shared with us [ 5 , 16 , 17 , 33 35 ], observations from previous Dutch studies [ 28 ], and on public discussions generated by the Dutch guideline on perinatal practice in extreme premature delivery [ 27 ]. This survey was improved in two Delphi rounds containing both four team members and two independent professionals.…”
Section: Methodsmentioning
confidence: 99%
“…The decision to begin life‐sustaining treatment (LST) on critically ill neonates is an internationally debated issue that continues to provoke widespread discussion . The care of babies born at the threshold of viability raises questions about their chances of survival and about their expected quality of life .…”
Section: Introductionmentioning
confidence: 99%